INDEX Home Contact Divisibility by 7 How to use log table Curve Tracing Collatz conjecture 2-D Geometry IIT JEE 2013 SOLUTION PAPER 1 Counter Curve Tracing

METHOD OF TRACING A CURVE

Whose equation is in Cartesian form.

1. Symmetry
(i) A curve is symmetrical about x-axis if the equation remains the  same by replacing y by
–y. here y should have even powers only.
For example y2 = 4ax.
(ii) It is symmetrical about y-axis if it contains only even powers of x  For example x2 = 4ay.
(iii)If on interchanging x and y, the equation remains the same then  the curve is
symmetrical about the line. y = x,     For example x3 + y3 = 3axy (iv) A curve is symmetrical in the opposite quadrants if its equation remains the
same when x and y replaced by –x and –y.  For example y = x

2. (a) Curve through Origin

The curve passes through the origin, if the equation does not contain constant term.
For example the curve y2 = 4ax passes through the origin.

2 (b)Tangents at the origin:
To know the nature of a multiple point it necessary to find the tangent at that point.
The equation of the tangent at the origin can be obtained by equating to zero, the lowest degree term in the equation of the curve.

3. The points of intersection with the axes

(i) By putting y= 0 in the equation of the curve we get the co-ordinates of the point of intersection with the x –axis.

(ii) By putting x = 0 in the equation of the curve; the ordinate of the point of  intersection with the y-axis is obtained by solving the new equation.

4. Regions in which the curve does not lie
.
If the value of y is imaginary for certain value of x then the curve does not exist for such values.
Example. y2 = 4x
Example. a2x2 = y3(2a - y).
For negative value of x, y is imaginary so there is no curve is second and third quadrant.
1. (i) For y> 2a x is imaginary so there is no curve in second and third quadrant
2. (ii) For negative values, of y, x is imaginary. There is no curve in 3rd and 4th quadrant.

5. Asymptotes are the tangents to the curve at infinity.
(a) Asymptote parallel to the x-axis is obtained by equating to zero, the coefficient of the highest power of x.
For example yx2 - 4x2 + x + 2 = 0
(y - 4)x2 + x + 2 = 0
The coefficient of the highest power of x i.e. x2 is y - 4 = 0
y - 4 = 0 is the asymptote parallel to the x axis.

(b) Asymptote parallel to the y-axis is obtained to zero, the coefficient of highest power of y.
For example
xy3 - 2y3 + y2 + x2 + 2 = 0
(x-2)y3 + y2 + x2 + 2 = 0
The coefficient of the highest power of y. i.e. y3 is x -2.
X -2 = 0 is the asymptote parallel to y-axis.

6. Tangent.
Put 0=dx/dy for the points where tangent is parallel to the x-axis.
For example x2 + y2 - 4x + 4y -1 = 0 ………(1)
2x +2ydxdy- 4 + 4dxdy= 0
(2y+4) dx/dy= 4 - 2x or dx/dy=4224+−yx
Now dxdy= 0. 4-2x = 0 or x = 2
Putting x =2 in (1), we get y2 + 4y -5 = 0
y= 1,- 5
The tangents are parallel to x-axis at the points (2,1) and (2, -5).

7. Table.
Prepare a table for certain values of x and y and draw the curve passing through them.

For example y2 = 4x +4

 x -1 0 1 2 3 Y 0 ±2 ±22 ±23 ±4

Example. Trace the curve y2( 2a – x ) = x3

Solution: y2= x3/( 2a – x ) ……..(1)
(i) Origin: Equation does not contain any constant term; therefore, it passes through origin.

(ii) Symmetrical about x-axis: Equation contains only even powers of y; therefore, it is symmetrical about x-axis.

(iii)Tangent at the origin: Equation of the tangent is obtained by equating to zero the lowest degree terms in the equation (1).
2ay2 - xy2 = x3
Equation of tangent:
2ay2 = 0 → y2 = 0

(v) Asymptote parallel to y-axis: Equation of asymptote is obtained by equating the coefficient of lowest degree of y.
2ay2 - xy2 = x3 or (2a-x)y2 = x3
Eq. Of asymptote is 2a-x = 0 or x = 2a.

(vi) Region of absence of curve: y2 becomes negative on putting x>2a or x<0, therefore, the curve does not exist for x<0 and x>2a. Some more Examples

Example. Trace the witch of Agnesi xy2 = a2(a-x). Example. Trace strophoid           x (x2 + y2 ) = a (x2 - y2 ) Example. Trace the Folium of Descartes   x3 + y3 = 3axy Example. Trace y2( a2 + x2 ) = x2( a2 - x2 ) Today, there have been 2 visitors (14 hits) on this page! Providing you complete maths solutions.